Towards a Traceability System Based on RFID Technology to Check the Content of Pallets within Electronic Devices Supply Chain - Ignacio Angulo; Asier Perallos; Leire Azpilicueta; Francisco Falcone; Unai Hernandez-Jayo; Asier Moreno; Ignacio Julio García Zuazola (International Journal of Antennas and Propagation)
In the last few years there has been a growing interest in smart solutions capable of dealing with the traceability of products and materials to improve logistical processes. Most of the existing solutions have been designed without considering the difficulties of deploying traceability systems in the storehouses currently working, not dealing with specific needs, such as environment characteristics or time required to be handled by workers. In this paper, in order to test the viability of its application, a first prototype of a traceability system capable of checking the content of pallets loaded with electronic devices is presented. It is based on ultra-high frequency (UHF) radio frequency identification (RFID) technology using passive tags. A holistic approach has been adopted to design the system: it begins with a radioelectrical characterization of the environment where the check points will be implemented, continues with the integration of a set of data acquisition and wireless communication devices, and ends with a logistics information system able to provide final user services. The combination of physical layer analysis with a top layer system view can aid the planning as well as operational phase of this type of RFID system within a logistic chain.